Diversification and determinants of banking performance: an international comparison - Jara Bertin, Mauricio; Arias Moya, José Tomás; Rodríguez Perales, Arturo (Estudios de Administración, 2011)
This paper analyzes the determinants of bank performance between Latin American and U.S. institutional environment. For a sample of 111 banks of six Latin American countries and the United States over the period 1997-2010, our results show the existence of significant differences in bank performance between the two institutional settings. Specifically, U.S. banks show higherperformance levels compared to Latin America, which may be explained by the greater administrative efficiency associated with total assets. On the other hand, our results show that thepredominant Latin American diversification through non-traditional banking activities has a positive effect on the performance of banks.